Divine and Human Love in Jewish and Christian Antiquity - Lincicum, David; Crabbe, Kylie (Mohr Siebeck, 2024)
Göttliche und menschliche Liebe in der jüdischen und christlichen Antike.
PublicationDate: 20241219
Keywords: New Testament -- ancient christianity -- Ancient Judaism -- theology of creation -- mercy -- Beten -- Love -- agape -- Korporatismus -- ancient Judaism -- ancient Christianity -- Altes Testament -- Neues Testament -- Kirchengeschichte -- Array